Handbook of research on the role of human factors in IT project management - Misra, Sanjay; Adewumi, Adewole (IGI Global, 2019)
The role humans play in the field of information technology continues to hold relevance even with the industry's rapid growth. People contribute heavily to the physical, cognitive, and organizational domain of computing, yet there is a lack of exploration into this phenomenon. Humanoid aspects of technology require extensive research in order to avoid marginalization and insufficient data. The Handbook of Research on the Role of Human Factors in IT Project Management is a collection of innovative research on the methods and applications of the task of human characteristics in the design and de
Description based upon print version of record
Description based on title screen (IGI Global, viewed 10/17/2019)
Keywords: Information technology / Management; Human-computer interaction; Project management